Clinical monitoring: infliximab biosimilar CT-P13 in the treatment of Crohn's disease and ulcerative colitis. (1st September 2016) - Keil, Radan; Wasserbauer, Martin; Zádorová, Zdena; Hajer, Jan; Drastich, Pavel; Wohl, Pavel; Beneš, Marek; Bojková, Martina; Svoboda, Pavel; Konečný, Michal; Falt, Přemysl; Vaňásek, Tomáš; et al.
Abstract: Objective: The infliximab biosimilar CT-P13 (Remsima ®, Inflectra ® ) was approved in Europe for the treatment of inflammatory bowel disease (IBD) based on extrapolation of data from patients with rheumatic disease. Because there are limited published reports on clinical outcomes for IBD patients treated with CT-P13, we monitored responses to induction treatment with this biosimilar in patients with Crohn's disease (CD) or ulcerative colitis (UC) in centres across the Czech Republic. Material and methods: Fifty-two patients with CD ( n = 30) or UC ( n = 22) were treated with 5 mg/kg CT-P13 for up to 14 weeks. Effectiveness of therapy was evaluated with the Crohn's Disease Activity Index (CDAI) or the Mayo Scoring System (MSS) in patients with CD or UC, respectively, before and after 14 weeks. Additional goals were to evaluate weight changes, serum C-reactive protein (CRP) levels, and complications/adverse events. Results: In patients with CD, remission (CDAI <150) was achieved in 50.0% of cases, and partial response (≥70-point decrease in CDAI score from baseline) in the remaining 50.0%. In patients with UC, remission (total score on partial Mayo index ≤2 points) was achieved in 40.9% of cases, partial response (≥2-point decrease in partial Mayo score from baseline) in 54.5%, and no response in 4.5%. There were statistically significant improvements in CDAI, MSS and CRP serum levels after 14 weeks of therapy, and body weight increased. Four adverse events were identified ( n = 1 each): lower-extremity phlebothrombosis, herpes labialis, pneumonia and allergic reaction. Conclusions: This prospective observational study provides evidence of the effectiveness of CT-P13 in IBD.